DESIGNING A SET OF INSTRUCTIONAL ENGLISH MATERIALS FOR SECRETARIAL STUDENTS - Dewi, Radeni Sukma Indra (PAWIYATAN, 2013)
This study is an attempt to find out what kinds of English materials are needed by secretarial students and their opinion about the existing English material, to describe how the Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â is developed in English teaching material for the secretarial students, finding out whether the Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â in English teaching material is effective and appropriate for the secretarial students of vocational school. Based on the research problems, this study is aimed to develop English teaching material, using Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â students textbook. It is done according to Standar Kompetensi Sekretaris in first grade of vocational school. The approach used in this study is Research and Development (R&D). I used all of the steps proposed by Hyland (2003:83). They are conducting survey, developing materials, expert and teacher validation, doing first revision, trying out, doing second revision, producing final product, and disseminating. The results show that Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â is worthwhile for the studentsÃ¢â¬â¢ achievement. We can see them from the results of their scores after being taught by using Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â students textbook. The final conclusions are as follows : First, the students said that they found it difficult with the existing English materials and sometimes they became bored. They needed an attractive materials such as English songs, or animated movies. Second, I developed material which is called Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â students textbook. This study can encourage the students to love English lessons. They can show their speaking and writing ability in business world. Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â not only can help the students save their beautiful mind and express their language in written or spoken form easily but it can also help the teachers to teach English more easily and in an enjoyable manner. Third, the students gave the interesting opinions about the developed material. All of them liked the material very much. The studentsÃ¢â¬â¢ achievement after being taught by using Ã¢â¬ÅEnglish for SecretaryÃ¢â¬Â is good.ÃÂ Keywords : Secretary, a Set of Instructional English Materials.